2021
DOI: 10.2174/1381612827666210303143442
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation and Cancer: The Role of Endothelial Dysfunction and Vascular Inflammation

Abstract: : Long-lasting subclinical inflammation is associated with a wide range of human diseases, particularly at middle and older age. Recent reports showed that there is a direct causal link between inflammation and cancer development, as several cancers were found to be associated with chronic inflammatory conditions. In patients with cancer, healthy endothelial cells regulate vascular homeostasis, and it is believed that they can limit tumor growth, invasiveness, and metastasis. Conversely, dysfunctional endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 127 publications
0
14
0
Order By: Relevance
“…It has been confirmed that chronic inflammation is an important cause of many malignant tumors, but its effect on the occurrence and development of breast cancer is still poorly understood (47). A variety of chronic inflammatory factors have been found to increase the risk of breast cancer, suggesting that chronic inflammation may play a role in the initiation and development of breast cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that chronic inflammation is an important cause of many malignant tumors, but its effect on the occurrence and development of breast cancer is still poorly understood (47). A variety of chronic inflammatory factors have been found to increase the risk of breast cancer, suggesting that chronic inflammation may play a role in the initiation and development of breast cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays a critical pathophysiological role in a wide range of pathological states, including cancer, diabetes, obesity, and neurodegenerative diseases ( Furman et al, 2019 ; Fois et al, 2020 ; Malhab et al, 2021 ). A significant body of research has provided strong evidence that resveratrol has anti-inflammatory properties by targeting transcription factors such as NF-kB and AP-1, and the gene COX-2 ( Meng et al, 2021 ).…”
Section: Inflammatory Statesmentioning
confidence: 99%
“…It is also a disease of autoimmune aseptic inflammation. Research shows that chronic inflammation is an indispensable participant in cancer development (3)(4)(5)(6)(7). Therefore, more and more research institutes begin to study the relationship between HT and cancer.…”
Section: Introductionmentioning
confidence: 99%